Identity, tradition and the city: Dichotomies and realities of creating an Urban language of the Malay palace - Raja Abdul Kadir, Tengku Anis Qarihah; Jahnkassim, Puteri Shireen; Abdul Latip, Nurul Syala (Malaysian Institute of Planners, 2018)
This paper highlights a case study, its critical issues and the processes encountered in the evolution and development of its urbanised grammar. In deriving a localised language in which traditional forms are fused and transmuted into masonry architecture, the case study of the "Istana Negara" Palace is a case in point. The issues triggered within the design process, including how to represent a universal Malaysian identity reflecting Malay Asian character with Islamic vocabulary are explored. The difficulties and realities of transmuting and integrating such vocabulary to express and configure public masonry buildings are discussed. As an icon for the city, the palace must reconcile its scale with a clear localised vocabulary to fulfil the symbolic nature of the design. The conflicts and dichotomies encountered include three aspects: 1) The dome vs pitch form as an icon for the city (from afar) and the need for a strong roof silhouette 2) the local grammar and language including the pedestal and architrave vocabulary and elements 3) the difficulty of proportionate form. The research points to the necessity and urgency of developing a set of compositional rules and elements of the language of Malay urban architectural identity derived from the essences of tradition and regional form.